Non-enzymatic Glycation of Almond Cystatin Leads to Conformational Changes and Altered Activity - A. Siddiqui, Azad; Sohail, Aamir; A. Bhat, Sheraz; T. Rehman, Md.; Bano, Bilqees (Protein and Peptide Letters, 2015)
The non-enzymatic reaction between proteins and reducing sugars, known as glycation, leads to the formation of inter and intramolecular cross-links of proteins. Stable end products called as advanced Maillard products or advanced glycation end products (AGEs) have received tremendous attention since last decades. It was suggested that the formation of AGEs not only modify the conformation of proteins but also induces altered biological activity. In this study, cystatin purified from almond was incubated with three different sugars namely D-ribose, fructose and lactose to monitor the glycation process. Structural changes induced in cystatin on glycation were studied using UV-visible spectroscopy, fluorescence spectroscopy, CD and FTIR techniques. Glycated cystatin was found to migrate slower on electrophoresis as compared to control cystatin. Biological activity data of glycated cystatin showed that D-ribose was most effective in inducing conformational changes with maximum altered activity.
Keywords: CD